Cellular dynamics during early barley pollen embryogenesis revealed by time-lapse imaging - Daghma, Diaa Eldin S.; Hensel, Goetz; Rutten, Twan; Melzer, Michael; Kumlehn, Jochen (Frontiers in Plant Science, 2014)
Plants display a remarkable capacity for cellular totipotency. An intriguing and useful example is that immature pollen cultured in vitro can pass through embryogenic development to form haploid or doubled haploid plants. However, a lack of understanding the initial mechanisms of pollen embryogenesis hampers the improvement and more effective and widespread employment of haploid technology in plant research and breeding. To investigate the cellular dynamics during the onset of pollen embryogenesis, we used time-lapse imaging along with transgenic barley expressing nuclear localized Green Fluorescent Protein. The results enabled us to identify nine distinct embryogenic and non-embryogenic types of pollen response to the culture conditions. Cell proliferation in embryogenic pollen normally started via a first symmetric mitosis (54.3% of pollen observed) and only rarely did so via asymmetric pollen mitosis I (4.3% of pollen observed). In the latter case, proliferation generally originated from the vegetative-like cell, albeit the division of the generative-like cell was observed in few types of pollen. Under the culture conditions used, fusion of cell nuclei was the only mechanism of genome duplication observed.